Shell-Thickness-Controlled Synthesis of Core-Shell Pd@Pt Nanocubes and Tuning of Their Oxygen Reduction Activities. Issue 2 (14th January 2017) - Yang, Chia-Chen; Liu, Zhe-Ting; Lyu, Yuan-Ping; Lee, Chien-Liang
Abstract : An approach to control Pt shell thickness in the synthesis of Pd@Pt core-shell nanocubes (NCs) has been successfully developed. Tuning the Pt and Pd precursor concentration ratio (Pt 4+ /Pd 2+ ) in the reaction mixture allowed precise control over the Pt shell thickness in the range of 0.3–4.9 nm. At low Pt 4+ /Pd 2+ ratios (≤1/4), the deposition of Pt occurred via a layer-by-layer mode, whereas layer-by-layer deposition followed by Pt island growth was possible at higher Pt 4+ /Pd 2+ ratios (1/3, 1/2, and 1). Additionally, rotating ring-disk electrode experiments determined the shell-thickness-dependent specific activities (SAs) and mass activities (MAs) of these Pd@Pt NCs, which acted as oxygen reduction catalysts in NaOH solution. Among these core-shell catalysts, the Pd1 @Pt1/6 NCs (0.3 nm Pt shell) displayed the highest SA (0.4398 mA cm –2 ) and MA (2.915 mA μg –1 ) values, which were 3.38 and 2.53 times higher than the corresponding values for Pt nanoparticles (SA = 0.13 mA cm –2, MA = 1.15 mA μg –1 ). These results, supported by X ray photoelectron spectroscopy observations, indicate that the high activity of Pd1 @Pt1/6 NCs is due to the modified electronic properties of the Pt shell influenced by the Pd NC core.